Стан інтродукційних популяцій видів роду Galanthus L. (Amaryllidaceae) флори Кавказу в умовах Києва. Частина 2. Широкоареальні види - Didenko, S.Ya. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
The work on introduction of some species belong to the genus Galanthus L. of the Caucasus flora have been conducted during 62 years on the botanical and geographical plot Caucasus of M.M. Gryshko National Botanical Garden of the NAS of Ukraine are shown. The results of two years study of snowdrops natural populations in the Caucasus are given.